From phallogocentric dominance to feminist epistemology: feminine authority in Rahadoost’s ‘I Still Can See’ - Zeiny, Esmaeil (Penerbit Universiti Kebangsaan Malaysia, 2025)
For centuries, Iranian women were literally absent or mentioned in passing in Persian literature. With the advent of modern thoughts and ways of living, women gained a presence in the male-dominated literature. The Iranian women questioned the traditional regulations, ventured into the public and expressed their thoughts and concerns through literature. However, the phallogocentrism dominating large parts of scholarship on literature has sidelined Iranian women and their literary contributions again. This phallogocentric order lost its momentum with the development of a different style, tone, and storytelling in women’s stories that challenge, transform, reconstruct and negotiate histories demonstrating women’s own identities, rights, and experiences. Drawing on the latest developments in feminist epistemology, particularly feminist standpoint theory on the significance of women’s everyday experiences and resistance, this paper examines Bahar Rahadoost’s text 'I Still Can See' (Rahadoost, 2023), shedding light on how Iranian women exercise feminine authority and construct "feminist knowledge." I argue that Rahadoost's text is an innovative genre and an epistemic repertoire that contests the official phallogocentric narratives that emphasise the importance of everyday experiences and forms of resistance in constructing feminist knowledge. This paper also illustrates how ‘I Still Can See’ makes an essential contribution to the global discourse on feminist epistemology.